Television News Production Training in Improving Soft Skills of Students of the Communication Studies Program, University of Muhammadiyah Jakarta - Fachri Septian; Aminah Swarnawati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Soft skills are abilities possessed by an individual naturally which include intelligence, both emotional and intellectual, communication, to socialization with other individuals. Higher education can be used as a forum to prepare students to face changes in social, cultural, world of work and rapid technological advances. The purpose of television news production training is to improve students' soft skills. The target of this training is students of the Communication Studies Program, University of Muhammadiyah Jakarta. The activity was carried out from March 24 to June 20, the stages of activity were research, preparation, implementation, evaluation and reporting. The result of the activity is that the soft skills of the participants are increased. Participants' knowledge of the technicalities of television news production and journalism increased after the discussion, and the enthusiasm of the participants increased after the short video production competition was held.